Narrowing of the neonatal region in the FBN1 gene. (14th October 2021) - Brogger, M N; Fernandez Ferro, G; Cardenas Reyes, I; Ochoa, J P; Garcia Hernandez, S; Valverde, M; Fernandez, X; Garcia Giustiniani, D; Lamounier, A; De La Higuera Romero, L; Ortiz Genga, M; Monserrat, L; et al.
Abstract: Background: Neonatal Marfan syndrome (MFS) is considered the most severe form of MFS and is characterized by early childhood death due to congestive heart failure. It has been suggested that genetic variants associated with this clinical presentation, cluster in a specific region between exons 24 and 32. It has been reported that patients carrying genetic variants in these exons have worse prognosis. Purpose: Our purpose was to analyze cardiovascular outcome by location of the genetic variants in the "neonatal region" of the FBN1 gene. Materials and methods: We analyzed clinical data on 1353 carriers and affected relatives with 683 missense pathogenic or likely pathogenic genetic variants of FBN1 gene (including cases identified in our laboratory and cases described in the literature) in whom age at last follow-up was available. Kaplan-Meier survival curves were generated to examine location of the genetic variant in the FBN1 gene in relation to survival free of surgical intervention or cardiovascular (CV) death (composite of deaths related to aortic dissection, heart failure/transplant, sudden, stroke or CV surgery). Missense genetic variants were classified as located in the "neonatal region" (residues 952–1363, corresponding to exons 24–32) and in the "non-neonatal region" (residues 45–951 and 1364–2731). In the "neonatal region", we have also analyzed a sub-region of "over-representation" of heart failure deaths in the first year of life, which we called "critical neonatal region" (amino acids 1028–1088, corresponding to exon 25 and few residues from exon 26) in comparison to the "non-critical neonatal region". Results: Data were examined on 1060 patients with missense variants located in the "non neonatal region" and on 293 patients with missense variants located in the "neonatal region". Of these, 96 patients were carriers of missense variants in the "critical neonatal region", the rest of patients carried variants in the neonatal region, outside this particular domain ("non-critical neonatal region"). Patients carrying missense variants in the neonatal region had worse prognosis than those carrying variants outside this region. This poorer outcome was due to events occurring in patients carrying variants in the "critical neonatal region" (see Figure). These patients had the worse prognosis (p=0.000108, vs. the other groups). Furthermore, events in the non-critical neonatal region were similar to other missense variants located outside the neonatal region. There were no differences in the "neonatal region" when analyzing by gender. Conclusion: In our cohort, the worse prognosis seen in patients carrying missense pathogenic or likely pathogenic variants in the "neonatal region" compared to the "non-neonatal region", was due to events in patients carrying missense variants in a small subregion which we called the "critical-neonatal region" (exons 25 and 26). These patients had the worse prognosis, irrespective of gender. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Health in Code